PENERAPAN MODEL TALKING STICK UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA SMP - Suhada (FKIP, Universitas Billfath Lamongan, 2020)
One of the teacher's tasks is to organize innovative learning by varying the learning model in the class. One learning model that can be used is a talking stick. Because according to preliminary observations it was found that students were not interested in natural science subjects, lacked motivation and low learning outcomes. This Classroom Action Research aims to find out: 1) Does the application of the talking stick model increase student motivation in junior high school science subjects ?; and 2) Can the application of the talking stick model improve student learning outcomes in junior secondary science subjects? This research was conducted in class VIII of SMP Negeri 11 Kota Bima in the 2017/2018 academic year from February to April 2018. The research was conducted in 2 cycles. Data analysis uses qualitative and quantitative data analysis. The results of the study: 1) the application of the talking stick model can increase student motivation in junior high school science subjects, because students who have high motivation and are very high in cycle II are 21 people or 91%. 2) the application of the talking stick model can improve student learning outcomes in junior high school science subjects, because students who successfully meet the minimum value of KKM 70 in cycle II are 21 people or 91%.